Fibre Bragg grating sensors in polymer optical fibres. (19th August 2015) - Webb, David J
Abstract: This review paper summarizes the current state of research into polymer optical fibre grating sensors. The properties of polymers are explored to identify situations where polymers offer potential advantages over more conventional silica fibre sensing technology. Photosensitivity is discussed and the sensitivities of polymer fibre gratings to strain, temperature and water are described. Finally, applications are reported which utilize the unique properties of polymer fibres.